Assessment of the Lequesne index of severity for osteoarthritis of the hip in an elderly population. - Dawson, J; Linsell, L; Doll, H; Zondervan, K; Rose, P; Carr, A; Randall, T; Fitzpatrick, R (2005)
OBJECTIVE: To assess the measurement properties of the Lequesne index of severity for osteoarthritis of the hip (LISOH) together with its overall usefulness with reference to the original stated aims. METHOD: Postal questionnaire was sent to a random sample of 5500 Oxfordshire residents, aged 65 and above. Respondents with hip symptoms at baseline (but without verification of a diagnosis) were sent an identical follow-up questionnaire 12 months later. The questionnaire included a general health section, including the Short Form-36 survey, and a hip section which began with a screening question about hip pain. Respondents who reported having a prolonged episode of hip pain were asked to complete the LISOH. RESULTS: At baseline, response rate of 66.3% (3341/5039) was obtained from eligible participants; 19.2% (610/3175) of respondents reported having hip pain. Internal reliability (Cronbach's alpha) was 0.84 (95% CI: 0.81-0.86) for all 11 items of the LISOH; however, factor analysis identified two factors (sub-scales): "function and mobility" and "pain and discomfort". Rasch analysis revealed that the two factors were only unidimensional when applied to sub-groups of respondents. Convergent validity of the LISOH was questionable, as the "function and mobility" factor was more highly correlated with SF-36 bodily pain score than was the "pain and discomfort" factor. The assessment of sensitivity over time was problematic due to changing patterns of symptomatic weight-bearing joints over time. CONCLUSIONS: The current study identifies major limitations with the LISOH--particularly if used as a single composite measure.